Sosialisasi Model Outdoor Learning Mathematics Project bagi Guru-Guru Matematika SMP di Jember - Pambudi, Didik Sugeng; Firmansyah, Frenza Fairuz; Anizah, Arinatul; Gantiyani, Hari (Perkumpulan Kualitama Edukatika Indonesia, 2025)
In general, mathematics learnings conducted in the classrooms and dominated by lecture methods. This results in students having a negative attitude towards mathematics, leading to low achievement. One alternative to make mathematics learning interesting for students is to use the Outdoor Learning Mathematics Project (OLMP). This model is believed to enhance motivation and academic performance among students. This community service activity aims to sosialize the OLMP model to mathematics teachers who are members of the Mathematics Teachers' Community (MGMP) in the Southern Jember region. The activity was conducted on 3 October 2024 with 43 mathematics teachers at SMPN 3 Balung Jember. The methods used included sharing information, discussion, assignments, observation, and the distribution of questionnaires. The results of the activity were very positive, with all participants able to understand the concept and benefits of the OLMP model for enhancing student motivation and academic performance. Participants were able to develop good and varied learning plans that included contexts such as (1) buying and selling at the school canteen and cooperative, (2) collecting data on the number and types of vehicles in the school parking lot, (3) measuring the length, width, area, and perimeter of the basketball court, (4) measuring the volume of trash bins and flower pots, and (5) measuring the height of flagpoles and trees on the school grounds. All participants gave positive feedback and suggested that this activity should be continued in the future to enhance teachers' professionalism.